Positive Politeness Strategies Used by the Main Character in the Movie It Ends with Us - Dewi, Baiq Kartika Purnama; Syamsurijjal; Sudewi, Ni Ketut Putri Nila; Syahid, Agus; Miswaty, Titik Ceriyani (Lexeme : Journal of Linguistics and Applied Linguistics, 2025)
This study analyzes the use of positive politeness strategies employed by the main character, Lily Bloom, in the film It Ends With Us (2024). Grounded in the politeness theory proposed by Brown and Levinson (1987), this qualitative descriptive research aims to (1) identify the types of positive politeness strategies used by or directed toward Lily Bloom and (2) examine which strategies are dominant and how they influence interpersonal relationships and the storyline’s progression. The data were drawn from selected dialogues involving Lily and were analyzed using content analysis techniques. The findings reveal that Lily uses various positive politeness strategies, including giving compliments, using inclusive pronouns, expressing gratitude, offering assistance, and showing empathy. The most frequent strategies include giving compliments, inclusive language, and expressions of gratitude. These strategies not only illustrate Lily’s attempt to build solidarity and closeness with others but also reflect her emotional resilience and interpersonal sensitivity in navigating complex social dynamics. The study contributes to the field of pragmatics by highlighting how politeness strategies serve as both linguistic and narrative tools in contemporary film discourse.